Faktor-Faktor Yang Memprediksi Purchase Intention Skin Care Garnier Di Indonesia - Clara Tanuwijaya; Frangky Slamet (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2021)
Brand awareness is the consumer's ability to remember a brand, brand association is a positive / negative perception when remembering a brand, perceived quality is a customer evaluation of brand superiority, brand loyalty is a customer commitment to a brand, and purchase intention is an evaluation of consumers to decide to buy a product. This study aims to determine the predictions of brand awareness, brand association, perceived quality and brand loyalty to purchase intention with a conclusive quantitative method and a cross-section study. Data obtained by means of a survey made with